RFID synchronisation for ambient services in a holonic and isoarchic control model. (1st January 2014) - Dubromelle, Yves; Prunaret, Jean-Pierre; Ounnar, Fouzia; Pujo, Patrick
RFID technologies will increase the capabilities to interact, to react and to customise control systems with innovative possibilities. New control approaches should be proposed based on the use of emerging technologies that will allow their operability in manufacturing systems. A model for ambient control production systems is proposed, based on a set of holonic entities interacting through a set of entities that offer ambient services. After describing the PROSIS (Product, Resource, Order, Simulation Isoarchic System) model, some of the ambient services and the way these services could be provided are presented. PROSIS is based on the holonic paradigm, an isoarchic structure and a multicriteria decision aid method. RFID technologies are used to synchronise the real-world entities (products, resources etc.) and their corresponding entities in the informational world according to the PROSIS model. Then, the impact of the proposed approach in terms of performance evaluation is studied.